2019
DOI: 10.1186/s43031-019-0007-8
|View full text |Cite
|
Sign up to set email alerts
|

Physics education research for 21st century learning

Abstract: Education goals have evolved to emphasize student acquisition of the knowledge and attributes necessary to successfully contribute to the workforce and global economy of the twenty-first Century. The new education standards emphasize higher end skills including reasoning, creativity, and open problem solving. Although there is substantial research evidence and consensus around identifying essential twenty-first Century skills, there is a lack of research that focuses on how the related subskills interact and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(104 citation statements)
references
References 80 publications
1
68
0
4
Order By: Relevance
“…Examining the research in the field of science education, it was seen that most teachings were realized by the teachers with the deductive method, and this was criticized in the literature (Bao & Koenig, 2019;Dykstra et al, 1992). Teaching by the deductive method is defined as teaching in which the teacher transmits theoretical information first and then presents mathematical models, and in which the process is completed by solving the exercises in the coursebook.…”
Section: Inquiry-based Learning Approach In Science Educationmentioning
confidence: 99%
“…Examining the research in the field of science education, it was seen that most teachings were realized by the teachers with the deductive method, and this was criticized in the literature (Bao & Koenig, 2019;Dykstra et al, 1992). Teaching by the deductive method is defined as teaching in which the teacher transmits theoretical information first and then presents mathematical models, and in which the process is completed by solving the exercises in the coursebook.…”
Section: Inquiry-based Learning Approach In Science Educationmentioning
confidence: 99%
“…In addition, this seemed has been more complicated along with the constantly changed curriculum applied. The lack of this mastering concept has been reported by a number of research (Bao & Koenig, 2019;Fernandez, 2017;Furwati & Zubaidah, 2017;Hayes & Kraemer, 2017;Hulwani et al, 2019;Putri et al, 2018). Most of the research have shown that students only solve Physics problems within low level of cognitive.…”
Section: Introductionmentioning
confidence: 95%
“…Learning models involving direct and practical activities are clearly needed to improve students' ability to understand the concepts of Physics. This research proposed constructive-based learning model which involves the sensory motor to enhance the improvement of concept acquisition (Bao & Koenig, 2019;Fernandez, 2017;Hayes & Kraemer, 2017;Nisa et al, 2018). One of the constructive-based learning models is Modelling instruction.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, physics education (PE) bears great potential in providing an excellent opportunity to drive and shape sustainable development for the future world. According to Bao and Koenig (2019), PE not only fosters high-end reasoning skills and improves students' scientific literacy competencies, but also produces technically literate, skilled workforce to support sustainable development.…”
Section: Introductionmentioning
confidence: 99%